1976
DOI: 10.2134/agronj1976.00021962006800060012x
|View full text |Cite
|
Sign up to set email alerts
|

Foam Application of Growth Retardants to Turfgrasses1

Abstract: Chemical growth retardants have been used on a limited scale to reduce mowing maintenance of turfgrasses. In recent years foam materials have served as carriers for pesticides and most recently for growth retardants. A foam carrier for retardants could offer the possible advantages of serving as an effective marker during application, reducing spray drift, and increasing growth retardant effectiveness. Four field studies were conducted in 1973 and 1974 at Carbondale, Ill. to compare foam application of growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1985
1985

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Most researchers, however, have either applied growth regulators to grass a few AGRONOMY JOURNAL, VOL. 76, JANUARY-FEBRUARY 1984 days after mowing (Elkins et al, 197 4;Aagesen and Elkins, 1976;Wu et al, 1976;Field and Whitford, 1980) or at a given height (Elkins, 197 4;Fales et al, 1976). Elkins (1974) found that growth regulators applied to tall fescue (Festuca arundinacea Schreb.)…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers, however, have either applied growth regulators to grass a few AGRONOMY JOURNAL, VOL. 76, JANUARY-FEBRUARY 1984 days after mowing (Elkins et al, 197 4;Aagesen and Elkins, 1976;Wu et al, 1976;Field and Whitford, 1980) or at a given height (Elkins, 197 4;Fales et al, 1976). Elkins (1974) found that growth regulators applied to tall fescue (Festuca arundinacea Schreb.)…”
Section: Discussionmentioning
confidence: 99%